Pakistan Rural Household Panel Survey 2012 (Round 1): Household characteristics - Nazli, Hina; Haider, Syed Hamza; Hausladen, Stephanie; Sheik, Asjad Tariq; Shafiq, Hassan; Shahzad, Saqib; Mehmood, Amina; Shahzad, Asma; Whitney, Edward (International Food Policy Research Institute, 2012)
This report presents the results of household data collected during the Rural Household Panel Survey (2012). The household survey collected information on a large number of topics, such as education, nature of employment, sources of income, time use, consumption patterns, economic shocks, and participation in social safety nets. The preliminary analysis presented in this report, provides an important baseline for understanding rural poverty. Most of the results of the RHPS-2012 presented in this report are in line with the findings of nationally representative household surveys.